Building a New Organizational Design for Multinational Enterprise - Priyanka Bedi, Ekta Kharbanda, (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper examined the modification in the conceptual frameworks which are used to understand and design MNEs. Disparity has been explored between traditional models and modern models which are signified as transnationalism and heterarchy. They are different in the sense that traditional models tend be the models of equilibrium which maintain stability at the macro level. But modern models tend to be the models of change and are applicable at the micro level. The purpose of this article is to make a proper contrast between these models by evaluating the consequences of switching from old to new models and at last endeavoring to reconcile and integrate traditional and modern models of MNE organizational design.